Characterization, classification and evaluation of soils of Kamrej Taluka in Surat district, Gujarat for sustainable land use planning - JANGIR, ABHISHEK; TIWARI, G.; SHARMA, R. P.; DASH, B.; PAUL, R.; VASU, D.; MALAV1, L. C.; TIWARY3, P.; CHANDRAN, P. (Journal of Soil and Water Conservation, 2021)
Detailed soil survey was conducted at 1:10,000 scale in the Kamrej taluka of Surat district, Gujarat for characterization, classification and evaluation of the land resources. Two landforms were demarcated in the area viz. lower and upper alluvial plains. Based on morphological, physical and chemical characterization, three soils series (Abrama, Digas and Sampura) were identified. Soils were developed from the basaltic alluvium parent material. The soils were very deep, slightly to moderately alkaline (pH 7.4 to 8.5), non-saline with low to medium in organic carbon (0.15 to 0.66%), low to high in calcium carbonate content (1.9 to 18.6%), medium to high CEC [40.2 to 63.6.0 cmol(p+)kg-1] and high base saturation (75 to 98%). The clay content of the soils varied from 37.4 to 52.8 per cent in surface horizons whereas it varied from 24.8 to 61.1 per cent in sub-surface horizons. Silt and sand content ranged from 12.7 to 39.5 and 16.8 to 54.8 per cent, respectively. The Abrama, Digas and Sampura soils were classified as fine, smectitic (calcareous) hyperthermic Typic Haplusterts; fine, mixed hyperthermic Vertic Haplustepts and fineloamy, mixed (calcareous) hyperthermic Typic Haplustepts, respectively. The area coverage of Abrama soils was 55.7 per cent, followed by Digas (19.7%) and Sampura (11.3%) soils. Soils were assessed as highly to marginally suitable for major crops (sugarcane, rice, wheat, banana and mango). The soil survey datasets can be extended to integrate biophysical data with socio-economic knowledge for sustainable land use planning in Kamrej taluka.